Efficacy Evaluation of Trichoderma Harzianum, T. Viride, & T. Asperellum: Eco-Biocontrol Agents Against Dry Rot of Potato in Pakistan - Shawal Shakeel; Gull-e-laala Khan; Gulshan Irshad; Nayla Haneef; Amna Maqsood; Salman Ghuffar; Nigarish Saghir (International Journal of Fungi, 2025)
Fusarium sambucinum is one of the most aggressive fusarium species initiating potato dry rot disease around the world and causing significant economic losses. To alleviate reliance on synthetic fungicides as their long-term use may lead to fungal resistance, biocontrol assays against threatening fungal diseases hold significant importance as an eco-friendly management approach. Antagonists are gradually becoming hotspots and hold broad applicable prospects. Trichoderma harzianum, T. viride, and T. asperellumwere screened for their biocontrol action against highly pathogenic isolates of F. sambucinum causing dry rot of potato in Pakistan. In vitro dual culture assay, observed after incubation at 27°C for one week, showed that all three tested Trichoderma species considerably inhibited the radial growth of F. sambucinum as compared to the control treatment where no visible fungal mycelial inhibition was recorded. Our results revealed that using antagonists against globally threatening fungal diseases may enhance the quality and production of important cash crops by generating handsome revenue.
Keywords: Biocontrol agents; Fusarium sambucinum; T. asperellum; T. viride; Trichoderma harzianum